Interaction Between Sex and Cardiac Interoceptive Accuracy in Measures of Induced Pain - Ferentzi, Eszter; Geiger, Mattis; Mai-Lippold, Sandra A.; Köteles, Ferenc; Montag, Christian; Pollatos, Olga (Frontiers in Psychology, 2021)
Pain perception is influenced by several factors, and among these, affect, sex, and the perception of bodily signals are assumed to play a prominent role. The aim of the present study is to explore how sex, cardiac interoceptive accuracy, and the interaction of the latter two influence the perception of experimentally induced pain. We investigated a large sample of young adults (n = 159, 50.9% female, age: 23.45, sd = 3.767), assessing current affective state with the Positive and Negative Affect Schedule, cardiac interoceptive accuracy with the mental heartbeat tracking task, and pain sensitivity with electrical stimulation on the back of the dominant hand applying a repeated measures staircase protocol. After controlling for the current affective state, males showed a significantly higher pain threshold and tolerance level than females, whereas cardiac interoceptive accuracy was not associated with pain sensitivity. The impact of the sex x cardiac interoceptive accuracy interaction was significant for pain threshold only; while pain tolerance was predicted only by sex. According to these findings, the associations between pain sensitivity, cardiac IAc, and sex might be more complicated than it was supposed in previous studies. Interactions between factors impacting pain perception appear worthy of further investigation.